In vivo Regeneration of Mineralized Bone Tissue in Anisotropic Biomimetic Sponges - Serrano-Bello, Janeth; Cruz-Maya, Iriczalli; Suaste-Olmos, Fernando; González-Alva, Patricia; Altobelli, Rosaria; Ambrosio, Luigi; Medina, Luis Alberto; Guarino, Vincenzo; Alvarez-Perez, Marco Antonio (Frontiers in Bioengineering and Biotechnology, 2020)
The last two decades, alginates have been validated as extracellular matrix analogues for tissue engineering. However, relevant lacks still concern their ability to mimic tissue microenvironment in terms of structural anisotropy. Hence, an increasing attention towards the fabrication of macro/microporous sponges able to support bone tissue defect regeneration by mimicking cell niche structure and bioactive functionalities. Herein, it was proposed the in vivo study of alginate sponges with anisotropic microporous domains (MAS) formed by ionic crosslinking in the presence of hydroxyapatite (HA) with different fractions (30% or 50% v). In comparison with unloaded sponges, we demonstrated that HA confers peculiar physical and biological properties to the MAS depending upon the inorganic fraction used, concurring to biomimetically support the regeneration of bone. SEM analysis showed a preferential orientation of pores, ascribable to the physical constrains exerted by HA particles during the pore network formation. EDAX and XRD confirmed a chemical affinity of HA with the native mineral phase of the bone. In vitro studies via WST-1 assay showed a higher adhesion and proliferation of hDP-MSC due to the presence of the bioactive HA signals. Moreover, in vivo studies – via micro-CT and histological analyses on bone model (e.g., rat calvaria defect) - confirmed a highest osteogenic response of MAS30 after 90 days, with a good regeneration of the calvaria defect without any evidence of the inflammatory reaction. Hence, all the results suggested the use of MAS as promising scaffold to support the regeneration of hard tissues in different body compartments.